JC Virus Regulatory Region Tandem Repeats in Plasma and Central Nervous System Isolates Correlate with Poor Clinical Outcome in Patients with Progressive Multifocal Leukoencephalopathy - Pfister, Luz-Andrea (American Society for Microbiology, 2001)
JC virus (JCV), the causative agent of progressive multifocal leukoencephalopathy (PML), has a hypervariable regulatory region (JCV RR). A conserved archetype form is found in the urines of healthy and immunocompromised individuals, whereas forms with tandem repeats and deletions are found in the brains of PML patients. Type I JCV RR, seen in MAD-1, the first sequenced strain of JCV, contains two 98-bp tandem repeats each containing a TATA box. Type II JCV RR has additional 23-bp and 66-bp inserts or fragments thereof and only one TATA box. We cloned and sequenced JCV RR from different anatomic compartments of PML patients and controls and correlated our findings with the patients' clinical outcome. Twenty-three different sequences were defined in 198 clones obtained from 16 patients. All 104 clones with tandem repeats were type II JCV RR. Patients with poor clinical outcome had high proportions of JCV RR clones with both tandem repeats in plasma (54%) and brain or cerebrospinal fluid (85%). In those who became survivors of PML, archetype sequences predominated in these anatomic compartments (75 and 100%, respectively). In patients with advanced human immunodeficiency virus infection without PML, only 8% of JCV RR clones obtained in the plasma contained tandem repeats. These data suggest that the presence of tandem repeats in plasma and CNS JCV RR clones is associated with poor clinical outcome in patients with PML.